Analisis Representasi Matematis Mahasiswa Teknik Informatika Dalam Menyelesaikan Soal Riset Operasi - Shofia, Niska (Universitas Nusantara PGRI Kediri, 2019)
Mathematical representation is very necessary for understanding concepts and solving mathematical problems, which can improve students' mathematical communication skills and play a role in improving mathematical competence. In the Department of Informatics, one of the compulsory subjects that require mathematical representation is the Operational Research course. Mathematical representation is needed in solving the problems of Operations Research because Operational Research uses mathematical models as a problem-solving approach. This study discusses the Analysis of Mathematical Representations in Completing the Transportation Problem in Operational Research Informatics Engineering students. The results of the analysis show that the mathematical representation of informatics students namely high-ability students can complete with multiple representations both representation visually and verbally and provide complete answers, but for low-ability students only provide visual representation only, and lack verbal representation and answers what is given is incomplete. And mathematical representation in solving operational research questions still needs to be improved.